Results of Remission Induction of 4'-O-Tetrahydropyranyladriamycin (THP) in the Children's Cancer and Leukemia Study Group 911 Study and 941 HR Pilot Study for Acute Lymphoblastic Leukemia - MIYAKE, Munenori; TSURUSAWA, Masahito; FUJIMOTO, Takeo; KAWAKAMI, Tetsuo; KAWAKAMI, Kiyoshi; WATANABE, Arata; IWAI, Asayuki; KIKUTA, Atsushi; NISHIKAWA, Ken-ichi; MIMAYA, Jun-ichi; KOIZUMI, Shouichi; SEKINE, Isao; et al. (The Japanese Journal of Pediatric Hematology, 1997)
To evaluate the safety of 4'-O-tetrahydropyranyladriamycin (THP), we examined the results of the so-called “911 study and 941 high-risk (HR) pilot study” of acute lymphoblastic leukemia (ALL) of the Children's Cancer and Leukemia Study Group. In the low-risk (LR) patients of the 911 study, THP was used. In the intermediate-risk (IR) patients of the 911 study and the HR patients of the 941 pilot study, THP and triple intrathecal injections (triple i. t., methotrexate 12.5 mg, cytarabine 30 mg, hydrocortisone 50 mg) were used. In the 911HR patients, triple i.t. was used. The rates of remission of the 911IR and 941HR pilot patients who used THP and triple i.t. were 88.2% and 91.9%, respectively. The rates of failure and chemotherapy interruption were 50.0% and 42.9%, respectively. The mean durations of granulocytepenia (<500/μl) were 20.4± 9.7 days and 24.8 ± 8.2 days, respectively. The rates of infection were 91.9% and 78.6%, respectively. The mean durations of thrombocytepenia (<50 × 103/μl) were 10.2 ± 8.0 days and 18.5 ± 10.4 days, respectively. All patients in the 911IR group who failed died because of infection. The mean duration length of thrombocytepenia in the 941HR pilot patients was significantly longer than the 911 HR patients. It should be recognized that THP and triple i. t.may cause severe bone marrow suppression in remission induction for ALL.